Analisis Aplikasi Yang Berjalan dan Rencana Proyek Dengan Metode New Information Economics Pada Asuransi Syariah AJB Bumi Putera 1912 - Bambang Zulkarnain (LPPM Universitas Dhyana Pura, 2015)
AJB Bumiputera 1912 is one of the Islamic insurance company, where the products themselves oriented life insurance. AJB Bumiputera 1912 has several application systems, infrastructure, services, and ongoing management (lights-on) as well as the projects being developed. Management Party wants to know the benefits and impacts of lights-on as well as projects inthe company and also the value of her tuning of the strategic direction. The author proposes to analyze lights on the project along with New Information Economics method using four practices, namely Strategic Demand / Supply Planning, Alignment, Innovation, and Prioritization. The results obtained by the SWOT matrix the company has four referral strategies, namely Enhance customer relationships, Expanding market share, increase work efficiency and Improve relations with business partners. While the lights-on who were in stable condition is a platform (hardware & software), Maintenance, Training, Budgeting and planning. Lights-on is in a state of enhanced only when needed is the application of sharia E-plus, office desktop, Helpdesk and Network. Lights-on who are in a satisfactory condition include BIL application of Sharia, Web GL, and the Portal Server. The project is a project that should take precedence over the VPN-IP then Datawarehouse, DRC and the SMS Service.Keywords : Application Analysis, Project Plan, New Information Economics Methods.